Significance, pharmacological properties, and industrial applications of bael (Aegle marmelos): A review of current knowledge - Farina Mujeeb; Ahamad Faiz Khan; Vinay Kumar Pandey; Ashapurna Sinha; Mukul Machhindra Barwant; Sarvesh Rustagi; Béla Kovács; Ayaz Mukarram Shaikh (Journal of Agriculture and Food Research)
The well-known traditional medicinal plant bael (Aegle marmelos) is used in many traditional medical systems, including Ayurveda, and may contain valuable compounds for industrial usage. The numerous health benefits of bael, including hepatoprotective, anti-inflammatory, antibacterial, and coumarin capabilities, are attributed to its bioactive constituents, including alkaloids, coumarins, and essential oils. One way to replicate the therapeutic capabilities of Bael across a wide range of illnesses in the pharmaceutical industry is to formulate bioactive compounds derived from Bael extracts and compounds into medicines for the treatment of diabetes, gastrointestinal problems, or skin ailments. Moreover, the food sector uses bael antioxidants and preservatives to enhance the nutritional value and shelf life of functional foods and drinks. To support green energy practices, plant byproducts have also been investigated for reclamation and biodegradable resources. Bael's integration into several businesses demonstrates the fruit's significant economic impact and highlights its significance in maintaining good health and leading a sustainable lifestyle. This study provides a thorough overview of Bael, focusing particularly on its potential commercial applications and biological uses.